Smart Home Automation Using Embedded Systems and AI Integration - Ali Imran (Global Journal of Multidisciplinary and Applied Sciences, 2024)
Smart home automation has become a major innovation in the 21st century, combining embedded systems and artificial intelligence (AI) to improve household efficiency, safety, and comfort. The integration of embedded microcontrollers with AI algorithms enables intelligent control of lighting, security, energy management, and entertainment systems. This study explores the architecture, components, and operational logic behind embedded-based smart home systems that leverage AI for decision-making and predictive control. The implementation of sensors, actuators, and wireless communication protocols such as Wi-Fi, Zigbee, and Bluetooth enables seamless connectivity between devices. AI-driven algorithms further enhance adaptability, allowing systems to learn user habits and optimize energy consumption. This paper provides a comprehensive overview of current trends, challenges, and future directions in smart home automation using embedded systems and AI integration.